Pembinaan Kesehatan Mental Peserta didik melalui Kegiatan Keagamaan - Ummu Habibah Rahmah; Siti Roudhotul Jannah; Jaenullah Jaenullah; Dedi Setiawan (Kuras Institute, 2022)
Mental health is a mental state or psychological state that shows a person's ability to make adjustments or problem solving to problems that exist within oneself (internal) and problems that exist in the external environment (external). Mental health refers to the way individuals think, feel and act that are efficient and effective in dealing with life's challenges and life stressors. Religious activities are an important means of fostering a healthy mentality. The phenomenon of mental health that occurs among students is very concerning. For example, stress, depression, anti-social behavior, and other psychological problems experienced by students. Therefore, it is necessary to develop students' mental health from an early age. This study uses a qualitative approach. The author's research report contains data excerpts to provide an overview of the complete presentation of the report. Based on the research above, this research is directed at fostering the mental health of students through religious activities at SD NU Metro. This observation was carried out by observing and taking notes directly on the object of research, namely by observing the activities in SD NU Metro City. Interviews were conducted by asking the principal, teachers and students at the educational institution. The results of the study indicate that the concept of mental health development is related to the concept of healthy human nature both physically, spiritually and mentally, which is based on the Qur'an and Hadith as well as the thoughts of Muslim and Western psychologists, as manifested in its definition, namely the realization of harmony between mental functions. and the creation of self-adjustment between the individual and his environment, based on faith and piety, to achieve a meaningful and happy life in this world and in the hereafter. Mental health coaching through religious exercises and habituation since childhood, exemplary through commendable behavior from the school environment, providing experiences through religious activities, and evoking the emotions of students in believing in Islam. Religious activities carried out at NU Metro Elementary School have a good influence on fostering the mental health of students who are instilled from an early age.